Numerical Determination of Permeability and Interfacial Convective Heat Transfer Coefficient for Non-Isotropic and Periodic Dual Scale Porous Medium - Sabet, Safa; Barışık, Murat; Sabet, Safa; Mobedi, Moghtada (Izmir Institute of Technology, 2015)
In this study, the fluid flow and heat transfer in a periodic, non-isotropic dual scale porous media consisting of permeable square rods in inline arrangement is analyzed to determine permeability and interfacial convective heat transfer coefficient, numerically. A periodical representative elementary volume (REV) with the dimensions of H×H is chosen as the computational domain. The flow in the REV is assumed fully developed and periodical. The permeable square particles are placed with in-line arrangement. There are two symmetrical intraparticle pores considered here which are in longitudinal flow direction. The continuity, Navier-Stokes and energy equations are solved to obtain the velocity, pressure and temperature distributions in the unit structures of the dual scale porous media. The obtained fields are upscaled by using volume average method to obtain the intrinsic inter and intraparticle permeabilities, bulk permeability tensor, interfacial convective heat transfer coefficients and the corresponding Nusselt numbers of the dual scale porous media for different values of inter and intraparticle porosities. The study is performed for interparticle porosities between 0.4 and 0.75 and for intraparticle porosities range of 0.2 to 0.8. A correlation based on Kozeny-Carman theory in terms of interparticle and intraparticle porosities and permeabilities is proposed to determine the bulk permeability tensor of the dual scale porous media. The intraparticle porosity value increase the flow rate passes through the porous media and the particle becomes more permeable. However; for high interparticle porosity values, the intraparticle porosity does not have importance effect on bulk permeability. Additionally, the results predicts that the interfacial convective heat transfer coefficient increases with increase of Reynolds number and the ratio of intra to interparticle porosity, while the increase rate shows variation with the porosity ratio and Reynolds number values.

Bu çalışmada, çizgi düzleminde geçirgen kare çubuklardan oluşan periyodik ve izotropik olmayan çifte seviye gözenekli ortamda akışkan akışı ve ısı transferi analizi yapılmıştır. Geçirgenlik ve arayüzey taşınım ısı transfer katsayısı sayısal olarak belirlenmiştir. Bir periyodik öz temsili hacim (ÖTH) H×H boyutlarında hesaplama alanı olarak seçilmiştir. ÖTH’deki akış tam gelişmiş ve periyodik varsayılmıştır. Geçirgen kare parçacıklar çizgi düzleminde yerleştirilmiştir. Uzunlamasına ve akış yönünde düşünülen iki simetrik parçacık içi gözenekler vardır. Süreklilik, Navier-Stokes ve enerji denklemleri çifte seviye gözenekli yapıda hız, basınç ve sıcaklık dağılımlarını elde etmek için çözülmüştür. Elde edilen sonuçlar parçacık içi ve arası geçirgenliği, toplu geçirgenlik tensörü, arayüzey taşınım ısı transferi katsayılarına karşılık gelen Nusselt sayılarını elde etmek için farklı parçacık içi ve arası gözeneklilik değerleri için hacimsel ortalama yöntemi kullanılarak elde edilmiştir. Çalışma, 0.4 ve 0.75 arasında parçacık içi gözeneklilik ve 0.2 ile 0.8 aralığındaki parçacık arası gözeneklilik için gerçekleştirilmiştir. Parçacık içi ve arası gözeneklilik ve geçirgenliği açısından Kozeny-Carman teorisine dayalı bir ilişki, çifte seviye gözenekli ortamın toplu geçirgenliği tensörünü belirlemek için önerilmiştir. Parçacık içi gözeneklilik değerinin yükselmesi, akışkanın debisini arttırmakla birlikte gözenekli yapının daha geçirgen olmasını sağlamaktadır. Bununla birlikte; yüksek parçacık arası gözeneklilik değerleri için, parçacık içi gözenekliliğin toplu geçirgenliğe önemli etkisi olmadığı gözlemlenmiştir. Ayrıca, elde edilen sonuçlara göre arayüzey ısı taşınım katsayısı, Reynold sayısının artması ve parçacık içi ve arası gözeneklilik oranı ile artar, artış oranı ise gözeneklilik oranı ve Reynold sayısı değerleri ile değişimini göstermektedir.
Geçirgenlik ve Arayüzey Isı Taşınım Katsayısının İzotropik Olmayan, Periyodik ve Çifte Seviye Gözenekli Yapı için Sayısal Olarak Belirlenmesi
Thesis (Master)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2015
Includes bibliographical references (leaves: 71-73)
Text in English; Abstract: Turkish and English
xii, 73 leaves
Keywords: Dual scale porous medium; Numerical simulation; Permeability; Kozeny-Carman Equation; Heat--Transmission